Penyuluhan Kebijakan Pengelolaan Sampah Di Area Wisata Kota Bengkulu - Faridah, Faridah; Mentari, Delta Purna; Rahman, Abi Fathur; Pamungkas, Aji; Saputra , Anggi (Jurnal Kewirausahaan dan Bisnis, 2021)
Extension of waste management policies in Bengkulu City's tourism areas is a strategic effort to increase public awareness of the importance of maintaining environmental cleanliness. This article discusses the role of extension in educating the public about sustainable waste management policies in tourism destinations. Through a participatory approach, it aims to introduce environmentally friendly waste management concepts and encourage the adoption of more environmentally responsible behaviors. By analyzing effective extension strategies and the challenges faced, this article highlights the importance of collaboration between the government, tourism industry, and the community in creating a clean and sustainable environment in the tourist areas of Bengkulu City.